[Uzi ; Cuisine ; To save the people [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1989)
A controversy about illegal importation of guns by Congressmen. Focuses in the educational system and philosophy behind the kind of training young medical students. A feature on two young rich and educated women who have chosen the kitchen as their place of work.
Uzi (15 min.) -- Cuisine (13 min.) -- To save the people (15 min.)
VHS.
Keywords: Diaz, Benjie; Forest, Margarita Araneta; University of the Philippines (Manila). -- College of Medicine; Firearms -- Laws and legislations -- Philippines; Gun control -- Philippines; Medical education -- Philippines; Medicine -- Vocational guidance